Targeted Transcriptomics of Frog Virus 3 in Infected Frog Tissues Reveal Non-Coding Regulatory Elements and microRNAs in the Ranaviral Genome and Their Potential Interaction with Host Immune Response - Tian, Yun; Khwatenge, Collins N.; Li, Jiuyi; De Jesus Andino, Francisco; Robert, Jacques; Sang, Yongming (Frontiers in Immunology, 2021)
Background: Frog Virus 3 (FV3) is a large dsDNA virus belonging to Ranaviruses of family Iridoviridae. Ranaviruses infect cold-blood vertebrates including amphibians, fish and reptiles, and contribute to catastrophic amphibian declines. FV3 has a genome at ~105 kb that contains nearly 100 coding genes and 50 intergenic regions as annotated in its reference genome. Previous studies have mainly focused on coding genes and rarely addressed potential non-coding regulatory role of intergenic regions. Results: Using a whole transcriptomic analysis of total RNA samples containing both the viral and cellular transcripts from FV3-infected frog tissues, we detected virus-specific reads mapping in non-coding intergenic regions, in addition to reads from coding genes. Further analyses identified multiple cis-regulatory elements (CREs) in intergenic regions neighboring highly transcribed coding genes. These CREs include not only a virus TATA-Box present in FV3 core promoters as in eukaryotic genes, but also viral mimics of CREs interacting with several transcription factors including CEBPs, CREBs, IRFs, NF-κB, and STATs, which are critical for regulation of cellular immunity and cytokine responses. Our study suggests that intergenic regions immediately upstream of highly expressed FV3 genes have evolved to bind IRFs, NF-κB, and STATs more efficiently. Moreover, we found an enrichment of putative microRNA (miRNA) sequences in more than five intergenic regions of the FV3 genome. Our sequence analysis indicates that a fraction of these viral miRNAs is targeting the 3’-UTR regions of Xenopus genes involved in interferon (IFN)-dependent responses, including particularly those encoding IFN receptor subunits and IFN-regulatory factors (IRFs). Conclusions: Using the FV3 model, this study provides a first genome-wide analysis of non-coding regulatory mechanisms adopted by ranaviruses to epigenetically regulate both viral and host gene expressions, which have co-evolved to interact especially in the host IFN response.